John Smith is NOT boring! - Cap'n John the (slightly) fierce - Smith, Johnny (Scholastic, 2015)
John Smith may have the most boring name in the world but his life is anything but boring. Cap'n Black is on the loose. He's the meanest pirate that ever lived and there's only one person who can stand up to him. That's Cap'n John Smith, the fiercest pirate to sail the seven seas (sort of)
Keywords: Pirates / Juvenile fiction; Pirates; Adventure and adventurers; Fiction; Juvenile works; Adventure fiction; Humorous fiction; Kinderbuch